Challenges Faced by Bachelor Level Students While Speaking English - Gambhir Bahadur Chand (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
Speaking is regarded as an indicator of language proficiency in general. It is believed that a learner who can speak a particular language fluently is regarded as a proficient learner of that language. In the context of Nepal, the English language is taken as a foreign language and taught from elementary level to university level as a compulsory subject but Nepalese students in general and university students in particular, face a lot of difficulties in speaking English fluently. Even after completing their graduate degree, some of them could not speak a little bit of English. This present study tried to explore the difficulties faced by undergraduate level students and the possible causes of their difficulties in speaking skills. This is an empirical qualitative study in which the researcher adopted a questionnaire and semi-structured interview to collect data from 15 undergraduate level students studying at the University. The collected data were thematized and analyzed in terms of two broad categories: Difficulties and causes with four/four subcategories of the broad themes. The study explored mainly: personal, social, environmental, and linguistic problems for speaking difficulties and teacher and teaching, course content, overuse of mother tongue, poor schooling, and classroom culture as the causal factors of speaking deficiency. The study suggested creating a favorable environment, maximizing learner autonomy, changing teaching practices, revising courses, and conducting speaking activities time and again.